Quantification and speciation of mercury and selenium in fish samples of high consumption in Spain and Portugal - Cabanero, AI (2015)
Mercury (Hg) and selenium (Se) determinations were carried out to evaluate human exposure to those elements through fish consumption in Spain and Portugal. Atomic fluorescence spectroscopy (AFS) was applied in a cold vapor mode for total mercury quantification and was also hyphenated to gas chromatography (GC) to achieve the speciation of organomercurial species in fish samples. The results obtained show the highest concentration of Hg in swordfish and tuna (0.47 +/- 0.02 and 0.31 +/- 0.01 mug g(-1), respectively), and a much lower concentration in sardine, mackerel shad, and octopus (0.048 +/- 0.002, 0.033 +/- 0.001, and 0.024 +/- 0.001 mug g(-1), respectively). The determination of alkyl mercury compounds revealed that 93-98% of mercury in the fish samples was in the organic form. Methylmercury (MeHg) was the only species found in the three fish species with higher mercury content. Total selenium concentration was high in sardine, swordfish, and tuna (0.43 +/- 0.02, 0.47 +/- 0.02, and 0.92 +/- 0.01 mug g(-1), respectively), but low in mackerel shad and octopus (0.26 +/- 0.01 and 0.13 +/- 0.01 mug g(-1), respectively). Speciation of selenium compounds was done by high-performance liquid chromatography in conjunction with inductively coupled plasma mass spectrometry (LC-ICP-MS). Selenomethionine (SeMet) was the only selenium compound identified in the fish samples with higher selenium content. Among the fish species studied, sardine had the most favourable Se:Hg and SeMet:MeHg molar ratios; therefore, its consumption seems to be preferable.